2013
DOI: 10.1590/s1413-35552012005000069
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment rate, feasibility and safety of power training in individuals with Parkinson's disease: a proof-of-concept study

Abstract: | Background: It has been suggested that power training should be implemented in interventions in Parkinson's disease (PD). However, it is necessary to determine the feasibility and safety of training rapid movements in such individuals. Objectives: To determine the rate of recruitment of potential participants, the rate of attendance at training sessions, the levels of adherence to the intervention, and the rate of adverse events. Method: Patients with PD, users of the national public health system underwent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 37 publications
2
6
0
1
Order By: Relevance
“…Only one recent multi-center study investigating a single training session with a self-stabilizing robotic exoskeleton in individuals with SCI has reached a recruitment rate near 50% (i.e., 20 participants recruited among 46 screened for eligibility) [ 17 ]. Nonetheless, the recruitment rate of the present study compares relatively well to the rates reached in other feasibility studies investigating various task-specific gait-training programs offered to relatively homogeneous samples of individuals with neurological impairments (e.g., stroke = 6.7% [ 20 ], Parkinson disease = 11% [ 21 ]). In the present study, the most important reason (16 out of 35 potential participants = 46%) for not qualifying for the training program was due to musculoskeletal impairments with the leading cause being a reduced passive range of motion at the ankle, knee, or hip.…”
Section: Discussionsupporting
confidence: 74%
“…Only one recent multi-center study investigating a single training session with a self-stabilizing robotic exoskeleton in individuals with SCI has reached a recruitment rate near 50% (i.e., 20 participants recruited among 46 screened for eligibility) [ 17 ]. Nonetheless, the recruitment rate of the present study compares relatively well to the rates reached in other feasibility studies investigating various task-specific gait-training programs offered to relatively homogeneous samples of individuals with neurological impairments (e.g., stroke = 6.7% [ 20 ], Parkinson disease = 11% [ 21 ]). In the present study, the most important reason (16 out of 35 potential participants = 46%) for not qualifying for the training program was due to musculoskeletal impairments with the leading cause being a reduced passive range of motion at the ankle, knee, or hip.…”
Section: Discussionsupporting
confidence: 74%
“…This picture was also observed in other two Brazilian trials, which also investigated the recruitment rate and retention with individuals with neurological disorders, even though treatment was provided to the volunteers 7,12 . The first was a proof-of-concept design study with individuals with Parkinson Disease (PD), who were recruited in public health services 12 . The results showed that lack of interest was as one of the main obstacle while recruiting 12 .…”
Section: Discussionsupporting
confidence: 71%
“…The first was a proof-of-concept design study with individuals with Parkinson Disease (PD), who were recruited in public health services 12 . The results showed that lack of interest was as one of the main obstacle while recruiting 12 . Similarly, Scianni et al 7 conducted a clinical trial with acute stroke survivors (< 6 months), who were recruited from physical therapy out-patient clinics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Estima-se que aproximadamente 1% à 1,5% da população com mais de 65 anos apresenta DP, principalmente para o sexo masculino e com idade entre 50 e 60 anos [1]. Diante da perda de dopamina, em níveis baixos no cérebro, há uma redução de sinapses elétricas no tratocórtico espinhal, o qual é composto principalmente por axônios motores, associado à perda de fibras musculares do tipo II, responsáveis por contrações de movimentos rápidos, havendo, no entanto, o déficit de recrutamento de unidades motoras, gerando assim, significativa fraqueza muscular e bradicinesianos indivíduos parkinsonianos [2]. A eletromiografia é uma ferramenta de extrema importância na avaliação da condição muscular dos indivíduos portadores da DP, a qual nos permite verificar de uma forma mais precisa e quantitativa a condição neurofisiológica que causa os sintomas como tremor, movimentos incoordenados e desequilíbrio [3].…”
Section: Introductionunclassified